Immune-Related Adverse Events Predict the Efficacy of Immune Checkpoint Inhibitors in Lung Cancer Patients: A Meta-Analysis - Wang, Donghui; Chen, Cen; Gu, Yanli; Lu, Wanjun; Zhan, Ping; Liu, Hongbing; Lv, Tangfeng; Song, Yong; Zhang, Fang (Frontiers in Oncology, 2021)
Background: Immune-related adverse events (irAEs) have been reported to be associated with the efficacy of immunotherapy. Herein, we conducted a meta-analysis to demonstrate that irAEs could predict the efficacy of immune checkpoint inhibitors (ICIs) in lung cancer patients. Methods: Literature on the correlation between irAEs and the efficacy of immunotherapy in lung cancer patients were searched to collect the data on objective response rate (ORR), overall survival (OS), or progression-free survival (PFS) of the patients. These data were incorporated into the meta-analysis. Results: A total of 34 records encompassing 8115 patients were examined in this study. The irAEs occurrence was significantly associated with higher ORR (risk ratio (RR): 2.43, 95% confidence interval (CI) [2.06–2.88], p < 0.00001) and improved OS (hazard ratio (HR): 0.51, 95% CI [0.43–0.61], p < 0.00001), and PFS (HR: 0.50, 95% CI [0.44–0.57], p < 0.00001) in lung cancer patients undergoing ICIs. Subgroup analysis revealed that OS was significantly longer in patients who developed dermatological (OS: HR: 0.53, 95%CI [0.42-0.65], p < 0.00001), endocrine (OS: HR: 0.55, 95%CI [0.45-0.67], p < 0.00001), and gastrointestinal irAEs (OS: HR: 0.58, 95%CI [0.42-0.80], p = 0.0009) than in those who did not. However, hepatobiliary, pulmonary, and high-grade (≥3) irAEs were not correlated with increased OS and PFS. Conclusion: The occurrence of irAEs in lung cancer patients, particularly dermatological, endocrine, and gastrointestinal irAEs, is a predictor of enhanced ICIs efficacy.